A Study of Pre-Discharge Holter Monitoring in Patients of Acute Myocardial Infarction - Jalaly, Tariq; Uraiya, D; Chanchlani, Roshan (International Journal of Medical Research and Review, 2015)
Background: Increasing array of medical intervention available to modify the likelihood of developing recurrent episode of myocardial ischemia, it is important to identify patients of risk of provocable myocardial ischemia before discharge. Material Methods: It was a cross-sectional study carried out in a tertiary care hospital of central India, during July 2012 to October 2014. During the monitoring period, the patient was once subjected for 100-meter brisk walk. Result: Out of 64 cases, 6 (9.5%) cases developed ischemia during Holter, in male it was 5(10.2%) while in female it was 1(6.67%). 13.33% of cases with tobacco consumption developed ischemia on Holter monitoring and this was found to statistically significant (x2 = 5.36, p<0.05). Conclusion: After acute myocardial infarction, pre-discharge Holter monitoring (including brisk walk) is a good non-invasive method to detect ischemia in high risk patients (like consuming tobacco in any form).